Lugol Increases Lipolysis through Upregulation of PPAR-Gamma and Downregulation of C/EBP-Alpha in Mature 3T3-L1 Adipocytes - Cuellar-Rufino Sergio; Zepeda Rossana Citlali; Flores-Muñoz Mónica; Santiago-Roque Isela; Arroyo-Helguera Omar (Journal of Nutrition and Metabolism)
Overweight and obesity are defined as excessive and abnormal fat accumulation that is harmful to health. This study analyzes the effect of different concentrations of the lugol solution (molecular iodine dissolved in potassium iodide) on lipolysis in cultured 3T3-L1-differentiated adipocytes. The mature adipocytes were treated with doses from 1 to 100 µm of lugol for 0.5, 6, and 24 h. The results showed that mature adipocytes exposed to lugol decrease their viability and increase caspase-3 activity with a lethal dose (LD50) of 473 µm. In mature adipocytes, lugol decreased the total intracellular lipid content, being significant at doses of 10 and 100 µm after 6 and 24 h of treatment (P<0.01), and the accumulation of intracellular triglycerides decreased after 24 h of exposure to lugol (P<0.05). Lugol treatment significantly increases the release of glycerol to the culture medium (P<0.05). The levels of adipocyte-specific transcription factors C/EBP-α were downregulated and PPAR-γ upregulated after 30 min with lugol. These results indicate a lipolytic effect of lugol dependent on PPAR-γ and C/EBP-α expression in mature 3T3-L1 adipocytes.